Handbook of adhesives raw materials - Flick, Ernest W. (Noyes Publications, 1989)
Contains descriptions of more than 2,200 materials available to the adhesives industry. The book includes supplier addresses and a trade name index.
Revised edition of: Handbook of adhesive raw materials, c1982.
Includes index.
Keywords: Adhesives -- Catalogs.; Adhesives -- Handbooks, manuals, etc.; elektronické knihy; electronic books